2013
DOI: 10.1086/668827
|View full text |Cite
|
Sign up to set email alerts
|

Limited Oxygen Availability In Utero May Constrain the Evolution of Live Birth in Reptiles

Abstract: Although viviparity (live birth) has evolved from oviparity (egg laying) at least 140 times in vertebrates, nearly 120 of these independent events occurred within a single reptile taxon. Surprisingly, only squamate reptiles (lizards and snakes) are capable of facilitating embryonic development to increasingly advanced stages inside the mother during extended periods of oviducal egg retention. Viviparity has never evolved in turtle lineages, presumably because embryos enter and remain in an arrested state until… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
61
2
2

Year Published

2013
2013
2023
2023

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 52 publications
(70 citation statements)
references
References 19 publications
5
61
2
2
Order By: Relevance
“…We know the necessary conditions for oviposition and incubation (Mortimer 1990, Ackerman 1997, we recognize that some anthropogenic activities can disrupt nesting (Miller et al 2003) and have identified that delays to nesting can increase embryonic death (Rafferty et al 2011(Rafferty et al , 2013. However, we still lack a deeper understanding of how sea turtles select nest sites at intra-and inter-beach levels.…”
Section: Outputs By Species Ocean Basin and Publication Venuementioning
confidence: 99%
“…We know the necessary conditions for oviposition and incubation (Mortimer 1990, Ackerman 1997, we recognize that some anthropogenic activities can disrupt nesting (Miller et al 2003) and have identified that delays to nesting can increase embryonic death (Rafferty et al 2011(Rafferty et al , 2013. However, we still lack a deeper understanding of how sea turtles select nest sites at intra-and inter-beach levels.…”
Section: Outputs By Species Ocean Basin and Publication Venuementioning
confidence: 99%
“…2). Hypoxia is known to prolong preovipositional arrest, allowing us to compare embryonic development in this treatment to the hyperoxic and normoxic treatments (Rafferty et al 2013). Five or six days is about the longest period that can elapse between the expected oviposition date and the actual oviposition date in natural populations of leatherback turtles (Reina et al 2002;Rafferty et al 2011), so we used it to represent a period of extended preovipositional arrest.…”
Section: Experimental Designmentioning
confidence: 99%
“…An extremely low-oxygen (hypoxic) environment in the oviducts of gravid female turtles is known to maintain embryonic preovipositional arrest in utero. Active embryonic development only recommences following exposure to atmospheric oxygen levels after eggs are laid (Rafferty et al 2013). There is an ongoing influence of the environment on the subsequent completion of development of embryos, as well as on the fitness of emerged hatchlings (Lee and Hays 2004), through factors such as temperature (Booth 2006;Rafferty and Reina 2014), concentrations of respiratory gases (Wallace et al 2004), egg location within the nest (Ralph et al 2005), and sand moisture (Wallace et al 2004).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…In fact, the capacity for maternal-fetal gas exchange is thought to constrain the evolution of viviparity (Andrews and Mathies, 2000;Andrews, 2002;Parker et al, 2004;Parker and Andrews, 2006). Furthermore, in chelonians, limitations on gas exchange arrest development of the oviductal egg, with the result that the egg is laid at a very early stage of development (Rafferty et al, 2013).…”
Section: Evidence From Extant Reptilesmentioning
confidence: 99%